An Overview of the Role of Calcium/Calmodulin-Dependent Protein Kinase in Cardiorenal Syndrome - Junho, Carolina Victoria Cruz; Caio-Silva, Wellington; Trentin-Sonoda, Mayra; Carneiro-Ramos, Marcela Sorelli (Frontiers in Physiology, 2020)
Calcium/calmodulin dependent protein kinases (CaMKs) are key regulators of calcium signaling in health and disease. CaMKII is the most abundant isoform in the heart, although classically described as a regulator of excitation-contraction coupling, recent studies shown that it can also mediate inflammatory in cardiovascular diseases (CVDs). Among CVDs, cardiorenal syndrome (CRS) represents a pressing issue to be addressed, considering the growing incidence of kidney diseases worldwide. In this review, we aimed to discuss the role of CaMK as an inflammatory mediator in heart and kidney interaction by conducting an extensive literature review using the databases PubMed. Here we summarized the role and regulating mechanisms of CaMKII present in several quality studies, providing a better understanding for future investigations of CamKII in CVDs. Surprisingly, despite the obvious importance of CaMKII in the heart, very little is known about CaMKII in CRS. In conclusion, more studies are necessary to further understand the role of CaMKII in CRS.